TEACHER'S STRATEGIES IN TEACHING ENGLISH VOCABULARY TO YOUNG LEARNERS :A DESCRIPTIVE STUDY OF A TEACHER'S STRATEGIES IN ONE OF THE ENGLISH COURSE IN CIMAHI - Khusnul Khotimah, - (2010)
The research entitled "Teacher's Strategies in Teaching English Vocabulary to Young Learners (A Descriptive Study of a Teacher's Strategies in One of the English Course in Cimahi)" which is aimed to find out teacher's strategies in teaching English vocabulary to young learners and difficulties faced by the teacher during teaching and learning process. This research was a descriptive study which investigated one English teacher and 13 students of fifth grade in one of the English Courses in Cimahi as the respondents. The data were gained through classroom observation (video recording) and interview. They were analyzed qualitatively. The research findings showed that there were several strategies applied by the teacher in teaching English vocabulary to young learners: using Song, Drilling, Game, Questioning for Comprehension Checking Strategy or QCCS, Demonstration (one of the direct instruction strategy), and Visual scaffolding. The research also found some methods used by the teacher in teaching English vocabulary to young learners such as Total Physical Response (TPR), Communicative Language Teaching (CLT), and Direct Method. The difficulties faced by the teacher were teacher's limited English proficiency, problems in pronunciation, classroom management, students' learning style, and students' characteristics. From findings of the research, it can be concluded that teaching English vocabulary to young learners in that course still lack of teacher's strategies. Therefore, to achieve the learning effectively especially in teaching English vocabulary to young learners, it is necessary for the teacher to apply more than one strategies, methods, and activities. It is also recommended that further research is conducted with larger sample and longer time. Key Words: Teacher's Strategies, Teaching English to Young Learners, Vocabulary